Three new species and one new synonymy in the genus Phlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) - Pan, Yangyang; Pang, Siyu; Bian, Xun (Zootaxa, 2024)
In this paper, we describe three new species from Yunnan Province and propose one new synonym in the genus. To better understand the new species, we provided morphological illustrations of allied species. All specimens were deposited in Guangxi Normal University.